2019
DOI: 10.24193/jmr.34.1
|View full text |Cite
|
Sign up to set email alerts
|

Good Things Come to Those Who Binge: An Exploration of Binge-Watching Related Behavior

Abstract: The rise of Video-on-Demand (VoD) services on the media market has produced key mutations in the television series industry at all levels. The dynamics of the tripartite relation between production, distribution and consumption gained new forms when these new services broke the traditional lineage of television and adopted the aesthetics of media catalogs that users can access whenever and wherever they want. VoD portals have triggered a process of usage democratization that has led to the unprecedented popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It can be a very positive and highly exciting experience; however, it is important to remember that the said immersive character of binge-watching can also be conducive to the risk of addiction. Furthermore, the Uses and Gratification Theory emphasises that using new technologies, including binge-watching, can be a very entertaining activity that caters to an individual's specific needs [19,20,30,42,71].…”
Section: Discussionmentioning
confidence: 99%
“…It can be a very positive and highly exciting experience; however, it is important to remember that the said immersive character of binge-watching can also be conducive to the risk of addiction. Furthermore, the Uses and Gratification Theory emphasises that using new technologies, including binge-watching, can be a very entertaining activity that caters to an individual's specific needs [19,20,30,42,71].…”
Section: Discussionmentioning
confidence: 99%
“…The link between binge-watching and parasocial breakups is not, at present, well understood. Boca (2019) suggested that binge-watching may be associated with stronger feelings of sadness, anxiety, and frustration when there are no more episodes to watch. These feelings of distress are likely due to the way the TV watching format may condition viewers to view waiting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Socioecological model of health indicates that social and cultural phenomenons contribute to the variability of individual's health (Słońska, 1994). The development of streaming platforms led to growth of popularity of bingewatching and changed the way how people consume television (Boca, 2019). Similarly to other addictions to technologies, binge-watching could be perceived as a behavior which usually is not associated with high levels of social harm (Grzegorzewska and Cierpiałkowska, 2018;Ort et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The newest studies search for the answer how healthy way of spending free time can change into the problematic bingewatching. The occurrence of anti-health form of binge-watching could be related to the new construction of narrative created by streaming platforms, characteristics of video on demand platforms, and individual psychological predispositions to development of problematic use of media (Alter, 2017;Grzegorzewska and Cierpiałkowska, 2018;Boca, 2019;Brand et al, 2019). Research has shown that binge-watching is an event that is very engaging both emotionally and cognitively, which may lead to loss of control over the number of watched episodes (Schweidel and Moe, 2016;Flayelle et al, 2017;Granow et al, 2018).…”
Section: Introductionmentioning
confidence: 99%